การรับร่างรัฐธรรมนูญไทย 2540 ของสมาชิกรัฐสภา - นิพนธ์ ชายใหญ่ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The major purpose of this study was to find out the influencing factors in accepting the 1997 Constitution of Thailand of the members of Parliament, by setting the following hypothesis : the Parliamentary acceptance of the 1997 Constitution of Thailand had been influened by two highly significant factors, they are, 1. public opinions which are consist of the roles of political activist group, interest group, mass media, people, and 2. the domestically economic depression. The result of hypothesis test was that the public opinions which are consist of the role of political activist group, interest group, mass media, people, and the domestically economic depression are the two highly significant factors influencing the members of Parliament for accepting the Constitution.